ChemInform Abstract: Combined Theoretical and in situ Scattering Strategies for Optimized Discovery and Recovery of High‐Pressure Phases: A Case Study of the GaN—Nb2O5 System. Issue 23 (May 2016) - Woerner, William R.; Qian, Guang‐Rui; Oganov, Artem R.; Stephens, Peter W.; Dharmagunawardhane, H. A. Naveen; Sinclair, Alexandra; Parise, John B.
Abstract: Two new oxynitride phases are discovered in the title system by high‐pressure synthesis using state of the art crystal structure prediction theory and in situ synchrotron‐based X‐ray scattering.